PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL MELALUI KOMITMEN ORGANISASI DAN JOBRELEVANT INFORMATION SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada SKPD Kabupaten Bengkalis) - Saputra, Riki; Hasan, Amir; Diyanto, Volta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The present study aims to examine the budgetary participation and managerial performance relationship on . It also attempts to examine whether organization commitment and Job-Relevant Information mediate the budgetary participation and managerial performance relationship. To collect data of this study, survey questionnaires are used. From 68questionnaires were given to managers in a public sector organization, questionnaires with complete answers were 53 questionnaires (77,9%). A path analysis was utilized to examine the direct and indirect effects of budgetary participation on managerial performance. The analysis results indicate that budgetary participation and managerial performance have positive relationship and statistically significant. Budgetary participation also directly affects organization commitment and Job-Relevant Information. But budgetary participation did not indirectly affect managerial performance via the intervening variables of organization commitment and Job-Relevant Information. Keywords: budgetary participation, managerial performance, organization commitment, and Job-Relevant Information.